Low leucocyte, neutrophil and lymphocyte count (tri-low phenotype) in melioidosis: A predictor of early mortality - Nitin Gupta; Praveen Kumar Tirlangi; Prithvishree Ravindra; Rachana Bhat; Mukund Gupta; Carl Boodman; Adil Rashid; Chiranjay Mukhopadhyay (Current Research in Microbial Sciences)
Introduction: Melioidosis is a bacterial disease caused by Burkholderia pseudomallei, a gram-negative bacillus endemic to parts of Asia and Northern Australia. This study aimed to identify the role of total and differential leucocyte count in predicting 48-h mortality in patients with melioidosis. Methodology: This retrospective cohort study included patients diagnosed with culture-proven melioidosis at Kasturba Medical College between 2017 and 2023. Total leucocyte count (TLC), absolute neutrophil count (ANC), and absolute lymphocytic count (ALC) were classified into low (first quartile), medium (second and third quartile) and high (last quartile). The chi-square test was used to compare each group's early (48-h) mortality. Results: Of the 170 patients with culture-confirmed melioidosis, 24 patients died within 48 h. The mortality was significantly higher in those with low TLC, ANC and ALC. When all three parameters were found to be low (tri-low phenotype), the specificity in predicting mortality was 93.2 %. Conclusion: Low TLC, ANC and ALC are significant predictors of mortality among melioidosis patients. There is a need to explore new strategies to improve clinical outcomes among melioidosis patients with tri-low phenotype.